DAMPAK KEBIJAKAN ISPO (INDONESIAN SUSTAINABLE PALM OIL) TERHADAP PENINGKATAN PENDAPATAN PETANI KELAPA SAWIT SWADAYA - Amalia, Dwi Nurul (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2023)
The implication of the Indonesian Sustainable Palm Oil (ISPO) policy is that palm oil produced by farmers can meet international market standards. However, the number of farmers implementing ISPO in Jambi Province remains relatively small. Several issues faced by independent smallholder palm oil farmers in Jambi in implementing ISPO certification include: (1) Financial constraints – the cost of obtaining ISPO certification is often high, including audit costs, capacity building, and farm improvements (2) Technology and knowledge – many independent smallholders lack access to modern farming technology or the knowledge needed to meet ISPO standards. The purpose of this article is to analyze the factors influencing palm oil production and the impact of ISPO policy implementation on increasing the income of independent smallholder palm oil farmers in Jambi Province. The sample consisted of 30 independent farmers in Rasau Village, Merangin Regency, selected using stratified sampling. Criteria included farmers certified with ISPO, having 2–10 hectares of land, and more than five years of planting experience. The econometric model built was a simultaneous equations model, and data were processed using SAS for Windows 9.0. The results showed that palm oil production was significantly influenced by land area, number of seedlings, and amount of fertilizer. Farmers’ income was significantly influenced by fresh fruit bunch (FFB) production, FFB price, fertilizer price, and labor wages. The ISPO policy's impact on increasing independent farmers’ income in Jambi Province is seen through increases in oil palm land area, FFB production, and FFB prices, which are linked to higher farmer incomes. The application of ISPO fosters greater agricultural output and professionalization. Certified farmers have better job possibilities and more consistent economic returns. This connects with SDG 8's sustainable development goals. Aside from that, it touches on SDGs 12 and 13.